2015
DOI: 10.1111/efp.12174
|View full text |Cite
|
Sign up to set email alerts
|

A histological investigation of Oriental beech wood decayed by Pleurotus ostreatus and Trametes versicolor

Abstract: Chemical, light and electron microscopic studies were carried out on wood of Oriental beech (Fagus orientalis Lipsky) decayed by the white-rot fungi Pleurotus ostreatus and Trametes versicolor for 30, 60 and 120 days according to the modified European standard EN 113. Mass loss as well as lignin, cellulose and carbohydrate content were determined before and after fungal attack. There were no significant differences of wood mass loss and chemical composition between both fungi at the end of incubation. After ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 33 publications
2
33
0
2
Order By: Relevance
“…As high nitrogen concentrations stimulate polysaccharide breakdown, low nitrogen levels could promote selective lignin removal (Fenn and Kirk 1981;Reid 1983). In the present study and the study of Bari et al (2015b), the conditions of growth media were favorable for a simultaneous white rot and for the formation of bore holes and can thus be considered. Figure 2 shows the water absorption of extracted wood with different combinations of solvents.…”
Section: Fig 1 Mycelium Growth Of T Versicolor Fungus In the Extramentioning
confidence: 94%
See 3 more Smart Citations
“…As high nitrogen concentrations stimulate polysaccharide breakdown, low nitrogen levels could promote selective lignin removal (Fenn and Kirk 1981;Reid 1983). In the present study and the study of Bari et al (2015b), the conditions of growth media were favorable for a simultaneous white rot and for the formation of bore holes and can thus be considered. Figure 2 shows the water absorption of extracted wood with different combinations of solvents.…”
Section: Fig 1 Mycelium Growth Of T Versicolor Fungus In the Extramentioning
confidence: 94%
“…Goktas et al (2010) found that beech wood specimens had weight losses ranging between 12.00% and 30.29% as affected by T. versicolor. The percents of the three cell wall components of Oriental beech wood (cellulose, lignin, and hemicellulose) were decreased by T. versicolor (Bari et al 2015b).…”
Section: Fig 1 Mycelium Growth Of T Versicolor Fungus In the Extramentioning
confidence: 94%
See 2 more Smart Citations
“…The sections were stained using a mixture of Safranin 0.5% and Astrablue 0.3% in 1:1 ratio (Mohebby, 2003;Schweingruber et al, 2011;Bari et al, 2015). The stained samples were washed with distilled water for 1e3 min, dehydrated with a 95% and absolute ethanol series for 2e3 min.…”
Section: Ft-ir Spectroscopymentioning
confidence: 99%